Lived Experiences of Multi-Banked Bank Account Holders with a focus on Banks at Manda Hill Mall Lusaka, Zambia - Kanyamuna, Vincent (Advances in Social Sciences Research Journal, 2020)
Multi-banking among bank account holders is a trend that has been on the rise in the recent past. Even though most banks provide similar services, like money transfer, deposits, loans, safety vault keeping, insurance and other services, it is seen that consumers have preference to certain specific banks. The purpose of this study was to assess the lived experiences of multi-banked bank account holders at Manda Hill Mall Lusaka, Zambia. Data was generated from seven purposively sampled multi-banked account holders using; in-depth interviews, focus group discussions, informal discussions and observations. Factors that emerged contributing to multi-banking among account holders were fraternity, proximity, customer service, security and brand loyalty. The study concluded that most of the factors that influence multi-banking involve the attitude of the account holders, fraternity inclinations, security constraints and poor customer services. Thus, it is recommend that account holders and would be account holders should be accorded chance to be well informed and make independent decisions as to which bank to bank with. In addition, Banks need to improve their service provision and strengthen relationships with their customers. Further, there is need for the banks to keep moving with time and improving their brand to appealing international standards. Above all, there is need to enhance security to the satisfaction of the clients.